ANALISIS PROFITABILITAS PADA INDUSTRI TEKSTIL DAN PRODUK TEKSTIL DI INDONESIA - Eko Riyanto (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2020)
This study aims to analyze profitability in the relationship between structure and performance of the textile and textile product industry in Indonesia with an annual 2011-2014. The type of data used is secondary data obtained from the Badan Pusat Statistik (BPS) of Indonesia. This study employs panel data regression with Fixed Effect Model (FEM). This research uses panel data to see effect of concentration ratio (CR4), internal efficiency (XEF), output value growth (Growth), and labor productivity (Prod) on profitability (PCM).The results of this research shows that the structure of textile and textile product industry in Indonesia is high-moderate oligopoly, with an average value of CR4 is 60.93 percent. The results of the regression shows internal efficiency (XEF) and labor productivity (Prod) have a positive significant effect on the profitability (PCM). While the concentration ratio (CR4) and output growth (Growth) does not have a significant effect on the profitability (PCM).